A REVIEW ON KEY DISTRIBUTION USING QUANTUM CRYPTOGRAPHY (International Journal of Engineering Sciences & Management Research, 2017)
Cryptography in the past was used in keeping military information, diplomatic correspondence secure and in protecting the national security. However, the use was limited. Nowadays, the range of cryptography applications have been expanded a lot in the modern area after the development of communication means; cryptography is essentially required to ensure that data are protected against penetrations and to prevent espionage. Also, cryptography is a powerful mean in securing e-commerce. Cryptography is used to ensure that the contents of a message are confidentiality transmitted and would not be altered.